2015
DOI: 10.1017/s0029665115002438
|View full text |Cite
|
Sign up to set email alerts
|

The wasting continuum in heart failure: from sarcopenia to cachexia

Abstract: Conference on 'Nutrition and age-related muscle loss, sarcopenia and cachexia' Symposium 2: Mechanisms for loss of muscle mass, strength and clinical measurement of malnutrition and cachexiaThe wasting continuum in heart failure: from sarcopenia to cachexiaStephan von Haehling Sarcopenia (muscle wasting) and cachexia share some pathophysiological aspects.Sarcopenia affects approximately 20 %, cachexia <10 % of ambulatory patients with heart failure (HF). Whilst sarcopenia means loss of skeletal muscle mass and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
78
1
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 120 publications
1
78
1
7
Order By: Relevance
“…These changes include a switch in the muscle fibers types from fast type II to the slow type I fibers and a reduction in capillary density (33,34). This may result in reduced physical performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes include a switch in the muscle fibers types from fast type II to the slow type I fibers and a reduction in capillary density (33,34). This may result in reduced physical performance.…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of muscle wasting in patients with chronic diseases is not entirely clear yet. Signaling pathways may be different in healthy aging and in patients with chronic diseases with higher inflammatory load and thus more pronounced proteasome activity in patients with chronic disease, thus serving as a basis for active myofibril degeneration (34,39). Indeed, one of the hypotheses holds that inflammatory processes, which accompany many chronic diseases, may lead to metabolic changes.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 Although frailty lacks a consensus definition, it has been shown to be an important prognostic marker in LVAD therapy. [22][23][24] It is not surprising that low muscle mass, which correlates with frailty, was strongly associated with mortality in this data set.…”
Section: Discussionmentioning
confidence: 99%
“…have previously suggested that repeated administration of ghrelin may improve left ventricular function, exercise capacity, and reduce muscle wasting in patients with HF. Because the relevance of sarcopenia in the clinical picture of HF22 is growing and approximately 20% of HF patients with an average age of nearly 70 years may meet the criteria for diagnosing sarcopenia,23 ghrelin may be an interesting treatment strategy to tackle the wasting continuum in HF 24…”
Section: Discussionmentioning
confidence: 99%